2017
DOI: 10.3389/fncel.2017.00201
|View full text |Cite
|
Sign up to set email alerts
|

Loss of IRF2BP2 in Microglia Increases Inflammation and Functional Deficits after Focal Ischemic Brain Injury

Abstract: Ischemic stroke causes neuronal cell death and triggers a cascade of inflammatory signals that contribute to secondary brain damage. Microglia, the brain-resident macrophages that remove dead neurons, play a critical role in the brain’s response to ischemic injury. Our previous studies showed that IRF2 binding protein 2 (IRF2BP2) regulates peripheral macrophage polarization, limits their inflammatory response and reduces susceptibility to atherosclerosis. Here, we show that loss of IRF2BP2 in microglia leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Interestingly, stroke recovery occurs via IFN‐β, and the other repressors of the IRF2BP family (IRF2BP1 and IRF2BPL) are not able to compensate for IRF2BP2 deficiency. These data suggest a specific function for IRF2BP2 in IFN‐β signaling . In addition, the same group demonstrated that IRF2BP2 in microglia is necessary for the anxiety‐reducing effect of enhanced maternal care by suppressing IL‐1β expression in mice …”
Section: Irf2bp2 Protein As a Gene Expression Regulatormentioning
confidence: 85%
See 4 more Smart Citations
“…Interestingly, stroke recovery occurs via IFN‐β, and the other repressors of the IRF2BP family (IRF2BP1 and IRF2BPL) are not able to compensate for IRF2BP2 deficiency. These data suggest a specific function for IRF2BP2 in IFN‐β signaling . In addition, the same group demonstrated that IRF2BP2 in microglia is necessary for the anxiety‐reducing effect of enhanced maternal care by suppressing IL‐1β expression in mice …”
Section: Irf2bp2 Protein As a Gene Expression Regulatormentioning
confidence: 85%
“…They observed a worsening of atherosclerosis, and IRF2BP2 promoted an anti‐inflammatory M2 profile in macrophages . In a recent work from the same group, the loss of IRF2BP2 in the microglia caused an increased production of inflammatory cytokines . On the other hand, restoring IRF2BP2 expression reduced inflammation and, consequently, decreased the risk of coronary artery disease and stroke .…”
Section: Biological Function Of Irf2bp2 In the Immune Responsementioning
confidence: 94%
See 3 more Smart Citations